Undercover creatures - Kenah, Katharine (Columbus, OH : School Specialty Pub., 2005)
Describes the ways several different kinds of animals, including polar bears, geckos, moths, and others, camouflage themselves in the wild.
1.5
K-3
Keywords: Camouflage (Biology) -- Juvenile literature; Camouflage (Biology); Camouflage (Biology)